Pattern if sexually transmitted Disease among HIV-! Infected commercial sex workers in Ibadan, Nigeira (2004)
"This study evaluatcd the association of HXV-1 infection with some other sexually transmitted diseases (STDs) among fernaIe commercial sex workers. BIood samples were collected from 250 female commercial sex workers in Ibadan Oyo State, Nigeria and tested for the presence of HEV antibodies using ELISA and Western blot. Endocervical and high vaginal swab samples were also collected for microscopy and culture. The prevalence of HIV- 1 infection among CSWs in Ibadan, Nigeria was 25.6% with 2.8% having dual reactivity to HIV- 1 and HIV- 2. Bacterial vaginosis was the commonest STDs (32.8%) followed by herpes genitalis, vaginal candidiasis, gonorrhoea, trichornoniasis, chancroid,syphilis, tinea curiz, genital warts, Iympholgranuloma venerum (LGV) and scabics. Recurrcnt vaginal discharge, gcnital ulccr discascs as well as non-genital ulcer diseases (tinea curiz and scabies) were associated with increased risk of HIV infections. Access to prevention and prompt management of these STDs will reduce the spread of HIV."